Physicians' Perspectives on Vaccinations - Kędra, Kamila; Michalik, Izabela; Zarańska, Julia; Aab, Arkadiusz; Bielak, Maciej (Journal of Education, Health and Sport, 2023)
Protective vaccinations are crucial for preventing infectious diseases and their complications, offering a high safety profile and minimal adverse effects. However, vaccine hesitancy has emerged as a public health concern, leading to outbreaks of communicable diseases. This study aims to investigate the attitudes towards vaccinations among doctors and nurses, as well as their knowledge level and vaccination frequency. The research employed a cross-sectional design and collected data using an anonymous questionnaire. The study was conducted in southern Poland, involving Primary Healthcare Centers and hospitals. A total of 878 paper surveys were collected among 542 doctors and 336 nurses.